Applied magnetic : its rapid revolution. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2010)
A magnet in general is material that produced, or is operated by means of magnetism. The way materials respond at microscopic level to an applied magnetic field is known as magnetism. The magnetic field is invisible but is responsible for the most notable property of magnetism in producing force so that different poles will attract to each other while similar poles will repel each other. The source of magnetism can be found in a permanent magnet and a conductor that is applied by an electric current. This means that the electrical energy can be converted to the magnetic energy without any medium of transmission. Such relationship makes magnetics capable of producing mechanical energy from an electrical energy such as motors, solenoids and actuators. Vice versa, electrical energy can also be produced from the mechanical energy. The use of electromagnetic principle is more superior compared with other automation principles such as hydraulics since it is cleaner and easier to be controlled for a fast response. The revolution of this field has innovated commercial products such as pumps. compressors, fans, blenders. cutters, drillers, crushers, printers, rollers, etc. Thus, electromagnetics has emerged in a new era where everyone is talking about efficiency and energy consumption plus being environmental friendly and less costly innovations.